The Fulfillment of Citizens Rights of Spiritual Believers - Michael Jeffri Sinabutar; Hidayati Hidayati (UIN Sjech M. Djamil Djambek Bukittinggi, 2023)
The Lom Tribe is the oldest tribe in Bangka Belitung, commonly referred to as the Lom people. During the colonial administration, the Bangka Malays were divided according to their religion, namely the La Tribe for Malays who had embraced religion, and the Lom Tribe for Malays who did not yet receive a religion. This paper aims to reckon the efforts of fulfilling the rights of the Lom Tribe, focusing on two main questions: first, what is the strategy of the Lom Tribe to access public services, especially population administration, education, and marriage? Second, are there still discriminatory practices for the Indigenous People of the Lom Tribe in accessing public services? This study employs a qualitative approach with an ethnographic approach, which aims at revealing the socio-cultural meaning in a particular context. The results show that in accessing public services, indigenous peoples use an institutional approach, build networks with stakeholders at the local level, as well as through the Indonesian Supreme Council of Trustees (MLKI). Discriminatory practices are still found in accessing public services, both in population administration, education, and marriage services for the Lom Tribe. For this reason, the Constitutional Court Decision No. 97/PUU-XIV/2016 and Permendikbud 27/2016.